Break-even point analysis
This video will follow step-by-step sequence as the president of an organization, together with his management team, charts, uses, and analyzes a break-even graph to help in the decision of whether or not to engage in the production of a new product. The video has been specifically designed to introduce non-finance managers and supervisors to the concept of break-even point analysis.